Analysis of Primary School Teacher Academic Qualifications in Physical Education in Tanjungpinang City - Een Sumarni; Yudi Pratama (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Mataram, 2025)
Research on analysing academic qualifications and shortages of Physical Education Teachers at elementary school level in Tanjungpinang City was conducted from August to October 2023. This research aims to find out how many elementary school teachers in Tanjung Pinang City have an academic background in physical education subjects and what challenges elementary school teachers who do not have physical education experience face when implementing physical education activities. This research will use survey methods and quantitative descriptive data analysis with a percentage approach to analyse data based on the academic background of each teacher. The survey found that around 78% of elementary schools in Tanjungpinang City lack physical education teachers, their performance is very low, and physical education subjects are taught by teachers who are unqualified or do not meet qualifications in their fields. This affects student learning outcomes due to the teacher's lack of teaching skills. Therefore, to overcome the problem of qualifications and shortage of physical education teachers in Tanjungpinang City, it is necessary to provide workers from the region or graduates with physical education degrees. However, to produce graduates with a bachelor's degree in physical education, a well-accredited university is needed that can provide a physical education study program that can meet the needs of physical education teachers in Tanjungpinang.